Efficacy of Hyperbaric Oxygen Therapy in Systemic Lupus Erythematosus Patients Undergoing Maxillofacial Surgery - Eko Mukti Wibowo; Ganendra Anugraha; Agung Satria Wardhana (Universitas Airlangga, Surabaya, Indonesia, 2025)
Highlights SLE is the most common autoimmune disease that requires management after maxillofacial surgery. Hyperbaric oxygen therapy is a treatment that can help accelerate recovery in patients. Abstract Background: Systemic Lupus Erythematosus (SLE) is a common multifactorial autoimmune disease that carries a high risk of osteoporosis and fractures. The delivery of oxygen to the body's tissues through hyperbaric oxygen treatment (HBOT) promotes the healing of wounds and shortens the typical recovery time for patients. The way tissues react to illnesses and injuries can be altered by HBOT. Objective: This article aimed to determine the use of hyperbaric oxygen therapy (HBOT) post-maxillofacial surgery in SLE patients. Materials and Method: This research used a scoping review approach, accessing electronic databases like PubMed, Scopus, Science Direct, Elsevier, and Google Scholar. Discussion: SLE is characterized by producing various autoantibodies that interact with endogenous antigens, favoring widespread inflammatory injury. SLE impacts the immune system, diminishing its ability to defend against infections. Hyperbaric oxygen therapy refers to administering 100% oxygen to a patient inside a pressurized chamber with a pressure higher than one atmosphere at sea level. The surgical placement of the implant into the mandible or maxilla allows it to be retained during functional loading, as the bone integrates with the implant during growth. Conclusion: HBOT can improve the host response by activating inflammatory cells and ensuring optimal oxygen tension in people with SLE. This can help with osteogenesis and neovascularization, which fill empty spaces with new blood vessels or bone tissue.